2013
DOI: 10.1089/cbr.2012.1415
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Polo-Like Kinase 1 Induces Cell Cycle Arrest and Sensitizes Glioblastoma Cells to Ionizing Radiation

Abstract: Despite efforts to improve surgical, radiologic, and chemotherapeutic strategies, the outcome of patients with glioblastoma (GBM) is still poor. Polo-like kinase 1 (PLK1) is a serine/threonine kinase that plays key roles in cell cycle control and has been associated with tumor growth and prognosis. Here, we aimed at testing the radiosensitizing effects of the PLK1 inhibitor BI 2536 on eight GBM cell lines. For cell cycle analysis, T98G, U251, U343 MG-a, LN319, SF188, U138 MG, and U87 MG cell lines were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
2
18
0
1
Order By: Relevance
“…In line with our findings, several other studies reported that the combination of Plk1 inhibition with radiotherapy leads to synergistic cell killing in vitro in multiple cancer types such as breast cancer, NSCLC, cervical epithelial adenocarcinoma, medulloblastoma, osteocarcinoma, glioblastoma, Merkel cell carcinoma, colorectal cancer, bladder carcinoma, oral cancer, and esophageal squamous cell carcinoma [8,[28][29][30][31][32][33][34][35][36][37][38][39][40]. In vivo, Dong et al demonstrated a synergistic inhibition of tumor growth and prolonged median survival in a tumor xenograft murine model with glioblastoma stem cells after treatment with volasertib and radiation [38].…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, several other studies reported that the combination of Plk1 inhibition with radiotherapy leads to synergistic cell killing in vitro in multiple cancer types such as breast cancer, NSCLC, cervical epithelial adenocarcinoma, medulloblastoma, osteocarcinoma, glioblastoma, Merkel cell carcinoma, colorectal cancer, bladder carcinoma, oral cancer, and esophageal squamous cell carcinoma [8,[28][29][30][31][32][33][34][35][36][37][38][39][40]. In vivo, Dong et al demonstrated a synergistic inhibition of tumor growth and prolonged median survival in a tumor xenograft murine model with glioblastoma stem cells after treatment with volasertib and radiation [38].…”
Section: Discussionsupporting
confidence: 92%
“…PLK1 knockdown has been shown to enhance radiation efficacy in prostate and rectal cancer [39,40], head-and-neck squamous cell carcinoma [41], and medulloblastoma [42]. Its pharmacological inhibition by BI 2536 has also shown similar results [43,44]. Exposure of different GBM cells to GSK461364 before radiation has also resulted in an increase in their radiosensitivity, with DERs ranging from 1.40 to 1.53 [45].…”
Section: Discussionmentioning
confidence: 99%
“…(the SFs were between 33.6% and 69.7%) [16]. Thus, BI6727 at 50 nM was used in the combinatory chemo-irradiation treatment throughout.…”
Section: Discussionmentioning
confidence: 99%